2011
DOI: 10.1007/s00384-011-1333-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fat obesity on laparoscopic total mesorectal excision: more reliable indicator than body mass index

Abstract: VFO is proven to be a more reliable predictive factor than BMI in estimating early surgical outcomes for patients who underwent LTME. VFO is associated with fewer numbers of retrieved lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(123 citation statements)
references
References 36 publications
4
118
1
Order By: Relevance
“…One of the reasons that explain part of this disagreement may be the different definitions of VF used in the articles published: VF area or volume [11, 14-17], ratio between VF and subcutaneous fat area [10], ratio between VF and total fat area [12] and ratio between VF and body surface area [9]. In addition, the same definition, like for example VF area, has different cut-off points in different papers [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the reasons that explain part of this disagreement may be the different definitions of VF used in the articles published: VF area or volume [11, 14-17], ratio between VF and subcutaneous fat area [10], ratio between VF and total fat area [12] and ratio between VF and body surface area [9]. In addition, the same definition, like for example VF area, has different cut-off points in different papers [18].…”
Section: Discussionmentioning
confidence: 99%
“…Those guidelines recommend that less than 12 lymph nodes retrieved constitute the high-risk factors for recurrence and adjuvant chemotherapy is beneficial to those patients [23]. Some papers concluded that the number of nodes harvested from patients with higher VF was significantly smaller [14, 17, 21] and others did not agree with this conclusion [10, 12]. This difference of lymph nodes harvested that we found on CC patients can have 2 explanations: VF increases surgical difficulty presenting as a problem for the surgeon to perform an accurate oncologic dissection and fat tissue adhering to the mesentery and makes the identification of the lymph nodes difficult for the pathologist [18].…”
Section: Discussionmentioning
confidence: 99%
“…Visceral obesity was calculated as visceral fat area on the basis of a CT scan using dedicated software to estimate the adipose area at one or more predefined levels. 11,18,19 In contrast to visceral fat area, AFR is a simple ratio that illustrates the relationship between anterior abdominal wall fat and intra-abdominal fat. The ratio itself uses an intraabdominal diameter at a given level (the level of the umbilicus) and is not an estimation of total intra-abdominal fat.…”
Section: Discussionmentioning
confidence: 99%
“…Using CT scan assessments of visceral fat to define obesity, Ishii et al reported a significant increase in the duration of surgery and morbidity rate in visceral obese patients [21]. Kang et al [22] reported that the visceral fat area measured by CT could be used as a more accurate predictor of surgical complexity than BMI. Therefore, the BMI may not be an accurate estimate of visceral fat.…”
Section: Discussionmentioning
confidence: 99%